Quality and economic aspects of roofing slates in theTharpu area, Tanahu - Neupane, Naba Raj; Paudel, Lalu Prasad (Bulletin of the Department of Geology, 2011)
A preliminary study on the occurrence, quality and economic aspects of the slates was carried in the slate deposits of theTharpu area, west Nepal Lesser Himalaya. The area is covered by the Nourpul Formation, Dhading Dolomite and the BenghatSlates of the Lower Nawakot Group forming a broad synclinal structure. Three deposits of slates were identified in the area atSeratar (Nourpul Formation), Phapardanda (Nourpul Formation) and the Chipliswara (Benighat Slate). Samples from all threedeposits were analyzed by petrographic, X-ray diffraction and Physico-chemical testing methods. The study shows that the slatesare well foliated, splitable into thin and smooth slabs, and physico-chemically close to the ASTM and IS standard values. Thequantity of slate is good enough for mining economically.DOI: http://dx.doi.org/10.3126/bdg.v14i0.5438Bulletin of the Department of Geology Vol.14 2011, pp.43-50